E3 ligase Smurf1 protects against misfolded SOD1 in neuronal cells by promoting its K63 ubiquitylation and aggresome formation. Issue 12 (12th January 2022) - Dong, Lei; Liu, Liqun; Li, Yang; Li, Wenxuan; Zhou, Liying; Xia, Qin
Abstract: K63-linked polyubiquitination of the neurodegenerative disease-associated misfolded protein copper-zinc superoxide dismutase 1 (SOD1) is associated with the formation of inclusion bodies. Highly expressed E3 ligase Smad ubiquitylation regulatory factor 1 (Smurf1) promotes cellular homeostasis through the enhanced capability of aggregate degradation. However, it is not well explored the role of Smurf1 in the dynamics of SOD1 aggresomes. In this study, we report that Smurf1 promotes the recruitment of SOD1 to form aggresomes. Mechanistically, Smurf1 interacts with mutant SOD1 to promote aggresome formation by modification of its K63-linked polyubiquitination. Moreover, overexpressed Smurf1 enhances mutant SOD1 aggresome formation and autophagic degradation to prevent cell death. Thus, our data suggest that Smurf1 plays an important role in attenuating protein misfolding-induced cell toxicity by both driving the sequestration of misfolded SOD1 into aggresomes and autophagic degradation.